2010
DOI: 10.1248/bpb.33.1506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin on Rosiglitazone-Induced Cardiac Hypertrophy in Mice

Abstract: Thiazolidinediones (TZD) can cause adipose tissue accumulation and myocardial hypertrophy. This study aimed to determine if combined Metformin (Glucophage) and Rosiglitazone (Avandia) could reduce the risk of heart failure caused by Rosiglitazone in BALB/c mice. BALB/c mice were treated with oral Rosiglitazone/Metformin twice daily for four weeks. Metformin or Rosiglitazone alone and non-treated mice acted as double control. Myocardial hypertrophy and associated side effects of the combined therapy were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In contrast, some studies have shown that rosiglitazone, another PPAR-γ agonist, may induce cardiac hypertrophy in mice, through PPARγ-independent mechanisms. 41,44 Despite the debate regarding the effect of PPAR-γ agonists on the heart, our findings suggested that pioglitazone proved to have beneficial effects against cardiac remodeling. Obviously, these results encourage further clinical studies to validate the cardio-protective effects of pioglitazone in diabetic patients, especially those with concomitant nephropathy.…”
Section: Discussionmentioning
confidence: 72%
“…In contrast, some studies have shown that rosiglitazone, another PPAR-γ agonist, may induce cardiac hypertrophy in mice, through PPARγ-independent mechanisms. 41,44 Despite the debate regarding the effect of PPAR-γ agonists on the heart, our findings suggested that pioglitazone proved to have beneficial effects against cardiac remodeling. Obviously, these results encourage further clinical studies to validate the cardio-protective effects of pioglitazone in diabetic patients, especially those with concomitant nephropathy.…”
Section: Discussionmentioning
confidence: 72%
“…Therefore, cardiac dysfunction of mice that overexpress cardiomyocyte PPARγ may be due to fatty acid-mediated PPARα activation, which does not occur in the aMHC-Pparg;Ppara -/mice. 173 Nevertheless, there are mixed results on PPARγ-driven activation of PPARα with some studies showing that rosiglitazone increases PPARα expression, 178 although others showing reduced expression of PPARα-target genes. 179 Along these lines, previous studies have shown that activation of either PPARα or PPARγ in cardiomyocytes is associated with accumulation of acyl-carnitines and diacylglycerols in cardiomyocytes that lead to cardiac dysfunction, 112,173 although cardiac acyl-carnitine content was reduced in the aMHC-Pparg;Ppara -/mice.…”
Section: Combined Activation Of Pparα and Pparγmentioning
confidence: 99%